The SLCO1A2 -189_-188InsA polymorphism reduces clearance of rocuronium in patients submitted to elective surgeries - Costa, A. C.C. (2017)
Purpose: Rocuronium (ROC) is a neuromuscular blocker mainly eliminated by biliary excretion dependent on organic anion transporting polypeptide 1A2 (OATP1A2) hepatocellular uptake. However, the influence of SLCO1A2 (gene encoding OATP1A2) genetic polymorphism on ROC pharmacokinetics was never described before. The objective of this work was to evaluate the influence of genetic polymorphisms of SLCO1A2 on the pharmacokinetics of rocuronium (ROC). Methods: Patients undergoing elective surgeries under general anesthesia using rocuronium as a neuromuscular blocker were genotyped for SLCO1A2 polymorphisms in the coding region (41A>G, 382A>T, 404A>T, 502C>T, 516A>C, 559G>A, 830C>A, and 833delA) and in the promoter region (-1105G>A, -1032G>A, -715T>C, -361G>A, and -189_-188insA). Rocuronium pharmacokinetic parameters were estimated by non-compartmental analysis. Results: None of the patients had heterozygous or homozygous variant of 404A>T, 382A>T, 502C>T, 833delA, 830C>A, 41A>G, and -715T>C. A linkage disequilibrium was found between -1105G>A and -1032G>A genotypes. Patients genotyped as -A or AA (n = 17) for SLCO1A2 -189_-188InsA showed reduced total clearance of ROC compared to patients genotyped as −/− (n = 13) (151.6 vs 207.1 mL/min, p ≤ 0.05). The pharmacokinetics parameters of ROC were not significantly different between other SLCO1A2 genotypes. Conclusion: SLCO1A2 -189_-188InsA polymorphism is related to the reduced clearance of rocuronium in patients submitted to elective surgeries under general anesthesia. Trial registration: NCT 02399397 (ClinicalTrials.gov).